A Synthetic Small Molecule, LGM2605: A Promising Modulator of Increased Pro-Inflammatory Cytokine and Osteoclast Differentiation by Aggregatibacter actinomycetemcomitans Cytolethal Distending Toxin - Taewan J. Kim; Andrew S. MacElroy; Aleena Defreitas; Bruce J. Shenker; Kathleen Boesze-Battaglia (MDPI AG, 2024)
Our research explores the interplay between Aggregatibacter actinomycetemcomitans (Aa) cytolethal distending toxin (Cdt) and the host's inflammatory response in molar/incisor pattern periodontitis (MIPP). Cdt disrupts phosphatidylinositol-3,4,5-triphosphate (PIP3) signaling, influencing cytokine expression through canonical and non-canonical inflammasome activation as well as nuclear factor-κB (NF-κB) activation, leading to inflammation in MIPP. THP-1 differentiated macrophages (TDMs) exposed to Cdt exhibited an upregulation of pro-inflammatory genes and subsequent cytokine release. We analyzed the ability of a small molecule therapeutic, LGM2605, known for its anti-inflammatory properties, to reduce pro-inflammatory gene expression and cytokine release in Cdt-exposed and Aa-inoculated TDMs. LGM2605's mechanism of action involves inhibiting NF-κB while activating the Nrf2-transcription factor and antioxidants. Herein, we show that this small molecule therapeutic mitigates Cdt-induced pro-inflammatory cytokine expression and secretion. Our study also further defines Cdt's impact on osteoclast differentiation and maturation in MIPP. Cdt promotes increased TRAP+ cells, indicating heightened osteoclast differentiation, specific to Cdt's phosphatase activity. Cathepsin K levels rise during this process, reflecting changes in TRAP distribution between control and Cdt-treated cells. Exploring LGM2605's effect on Cdt-induced osteoclast differentiation and maturation, we found TRAP+ cells significantly reduced with LGM2605 treatment compared to Cdt alone. Upon LGM2605 treatment, immunocytochemistry revealed a decreased TRAP intensity and number of multinucleated cells. Moreover, immunoblotting showed reduced TRAP and cathepsin K levels, suggesting LGM2605's potential to curb osteoclast differentiation and maturation by modulating inflammatory cytokines, possibly involving Nrf2 activation. In summary, our research reveals the intricate connections between Cdt, pro-inflammatory cytokines, and osteoclast differentiation, offering novel therapeutic possibilities for managing these conditions.